Re-employment probabilities for Spanish men: what role does the unemployment benefit system play? - Stephen P. Jenkins; Carlos García-Serrano (Deutsches Institut für Wirtschaftsforschung (DIW), 2000)
We analyse the re-employment probabilities of almost 330,000 Spanish men aged 20-59 years who began a unemployment insurance (UI) spell between February 1987 and November 1991 using data derived from the national unemployment benefit administration database (SIPRE) and discrete time duration models with flexible baseline hazards. We show: (i) the level of UI benefits has a relatively small disincentive effect on re-employment rates; (ii) re-employment exit hazards increase as UI exhaustion approaches but, again, the effect is relatively small. (iii) Extensions to Unemployment Assistance eligibility lowered re-employment probabilities. Also (iv) there are clear seasonal and cyclical effects on re-employment rates, and (v) rates are much higher for those who enter UI from a fixed-term employment contract rather than permanent one, and (vi) for young workers. These results are consistent with other research drawing attention to the impact on unemployment of inflexibilities in Spanish labour market institutions, combined with low inter-regional mobility and reliance by many for support via their family.
Keywords: 330; Arbeitsuche; Arbeitslosenversicherung; Arbeitslosigkeit; Dauer; Schätzung; Spanien